Cultivation of an Obligate Fe(II)-Oxidizing Lithoautotrophic Bacterium Using Electrodes - Summers, Zarath M.; Gralnick, Jeffrey A.; Bond, Daniel R. (mBio, 2013)
Fe(II)-oxidizing aerobic bacteria are poorly understood, due in part to the difficulties involved in laboratory cultivation. Specific challenges include (i) providing a steady supply of electrons as Fe(II) while (ii) managing rapid formation of insoluble Fe(III) oxide precipitates and (iii) maintaining oxygen concentrations in the micromolar range to minimize abiotic Fe(II) oxidation. Electrochemical approaches offer an opportunity to study bacteria that require problematic electron donors or acceptors in their respiration. In the case of Fe(II)-oxidizing bacteria, if the electron transport machinery is able to oxidize metals at the outer cell surface, electrodes poised at potentials near those of natural substrates could serve as electron donors, eliminating concentration issues, side reactions, and mineral end products associated with metal oxidation. To test this hypothesis, the marine isolate Mariprofundus ferrooxydans PV-1, a neutrophilic obligate Fe(II)-oxidizing autotroph, was cultured using a poised electrode as the sole energy source. When cells grown in Fe(II)-containing medium were transferred into a three-electrode electrochemical cell, a cathodic (negative) current representing electron uptake by bacteria was detected, and it increased over a period of weeks. Cultures scraped from a portion of the electrode and transferred into sterile reactors consumed electrons at a similar rate. After three transfers in the absence of Fe(II), electrode-grown biofilms were studied to determine the relationship between donor redox potential and respiration rate. Electron microscopy revealed that under these conditions, M. ferrooxydans PV-1 attaches to electrodes and does not produce characteristic iron oxide stalks but still appears to exhibit bifurcate cell division. IMPORTANCE Electrochemical cultivation, supporting growth of bacteria with a constant supply of electron donors or acceptors, is a promising tool for studying lithotrophic species in the laboratory. Major pitfalls present in standard cultivation methods used for metal-oxidizing microbes can be avoided by the use of an electrode as the sole electron donor. Electrochemical cultivation also offers a window into the poorly understood metabolism of microbes such as obligate Fe(II), Mn(II), or S 0 oxidizers by replacing the electron source with the controlled surface of an electrode. The elucidation of redox-dependent behavior of these microbes could enhance industrial applications tuned to oxidation of specific metals, provide insight into how bacteria evolved to compete with oxygen for reactive metal species, and model geochemical impacts of their metabolism in the environment. Electrochemical cultivation, supporting growth of bacteria with a constant supply of electron donors or acceptors, is a promising tool for studying lithotrophic species in the laboratory. Major pitfalls present in standard cultivation methods used for metal-oxidizing microbes can be avoided by the use of an electrode as the sole electron donor. Electrochemical cultivation also offers a window into the poorly understood metabolism of microbes such as obligate Fe(II), Mn(II), or S 0 oxidizers by replacing the electron source with the controlled surface of an electrode. The elucidation of redox-dependent behavior of these microbes could enhance industrial applications tuned to oxidation of specific metals, provide insight into how bacteria evolved to compete with oxygen for reactive metal species, and model geochemical impacts of their metabolism in the environment.